Season of Birth and the Risk of Hip Fracture in Danish Men and Women Aged 65+ - Abrahamsen, Bo; Heitmann, Berit L.; Eiken, Pia A. (Frontiers in Endocrinology, 2012)
Vitamin D status in pregnant women has been linked to childhood bone mineral density in their offspring but it is unclear if effects extend to fracture risk in adulthood or even old age. As vitamin D levels in the population show pronounced seasonal variation in Denmark, we performed an epidemiological analysis of hip fracture rates as a function of season of birth, age and sex. We retrieved information on all hip fractures in the nine-year period between 1997-2005 in all men and women aged 65-95, excluded hip fractures that occurred in current and recent prednisolone users, and subsequently calculated fracture rates and relative risks. The analysis covered 541,109 men and 691,522 women. In women, we observed a small but statistically significant difference between fracture rates by season of birth for all age intervals expect the youngest (age 65-69). A similar pattern was seen in men, but this was only statistically significant in the two oldest age groups (age 85-89 and 90-95). These findings suggest that vitamin D availability in the first and second trimester of intrauterine life could have a small but lasting impact on bone health and the risk of osteoporotic fractures